A self-adaptive energy harvesting system. (22nd February 2016) - Hoffmann, D; Willmann, A; Hehn, T; Folkmer, B; Manoli, Y
Abstract: This paper reports on a self-adaptive energy harvesting system, which is able to adapt its eigenfrequency to the operating conditions of power units. The power required for frequency tuning is delivered by the energy harvester itself. The tuning mechanism is based on a magnetic concept and incorporates a circular tuning magnet and a coupling magnet. In this manner, both coupling modes (attractive and repulsive) can be utilized for tuning the eigenfrequency of the energy harvester. The tuning range and its center frequency can be tailored to the application by careful design of the spring stiffness and the gap between tuning magnet and coupling magnet. Experimental results demonstrate that, in contrast to a conventional non-tunable vibration energy harvester, the net power can be significantly increased if a self-adaptive system is utilized, although additional power is required for regular adjustments of the eigenfrequency. The outcome confirms that active tuning is a real and practical option to extend the operational frequency range and to increase the net power of a conventional vibration energy harvester.